The Circle of Learning: Individual and Group Processes - Chang, Ernest; Simpson, Don (Education Policy Analysis Archives, 1997)
We present a paradigm for modeling the processes found in individual and group learning. Using combinations of two dimensions, the first being whether the learner's activities are By-Oneself or With-Peers, and the second whether the process orientation is toward the Person as the focus of the learning or toward the Group as the focus, we derive four quadrants in Activity-Orientation learning space. These four quadrants represent: lectures, individual learning, concurrent learning, and collaborative learning. From these combinations of Activities versus Orientation, we can describe many characteristics of these different learning categories.